Ion Association in Lanthanide Chloride Solutions. Issue 37 (30th May 2019) - Finney, Aaron R.; Lectez, Sébastien; Freeman, Colin L.; Harding, John H.; Stackhouse, Stephen
Abstract: A better understanding of the solution chemistry of the lanthanide (Ln) salts in water would have wide ranging implications in materials processing, waste management, element tracing, medicine and many more fields. This is particularly true for minerals processing, given governmental concerns about lanthanide security of supply and the drive to identify environmentally sustainable processing routes. Despite much effort, even in simple systems, the mechanisms and thermodynamics of Ln III association with small anions remain unclear. In the present study, molecular dynamics (MD), using a newly developed force field, provide new insights into LnCl3 (aq) solutions. The force field accurately reproduces the structure and dynamics of Nd 3+, Gd 3+ and Er 3+ in water when compared to calculations using density functional theory (DFT). Adaptive‐bias MD simulations show that the mechanisms for ion pairing change from dissociative to associative exchange depending upon cation size. Thermodynamics of association reveal that whereas ion pairing is favourable, the equilibrium distribution of species at low concentration is dominated by weakly bound solvent‐shared and solvent‐separated ion pairs, rather than contact ion pairs, reconciling a number of contrasting observations of Ln III –Cl association in the literature. In addition, we show that the thermodynamic stabilities of a range of inner sphere and outer sphere LnCl x ( 3 - x ) + coordination complexes are comparable and that the kinetics of anion binding to cations may control solution speciation distributions beyond ion pairs. The techniques adopted in this work provide a framework with which to investigate more complex solution chemistries of cations in water. Abstract : Understanding the solution chemistry of the lanthanides : Enhanced sampling simulations reveal the thermodynamics and mechanisms of formation for inner and outer sphere lanthanide complexes in solution. Molecular dynamics (MD), using a newly developed force field accurately reproduces the structure and dynamics of Nd 3+, Gd 3+ and Er 3+ in aqueous chloride solutions when compared with calculations using density functional theory (DFT). The mechanisms for ion pairing change from dissociative to associative exchange depending upon cation size and weakly bound ion pairs are prevalent in solution.